Triage vital signs do not correlate with serum lactate or base deficit, and are less predictive of operative intervention in penetrating trauma patients: a prospective cohort study. Issue 7 (16th July 2012) - Caputo, Nicholas; Fraser, Robert; Paliga, Andrew; Kanter, Marc; Hosford, Karlene; Madlinger, Robert
Abstract : Background: Triage vital signs are often used to help determine a trauma patient's haemodynamic status. Recent studies have demonstrated that these may not be very specific in determining major injury. The purpose of this study was to determine if there is any correlation between triage vital signs, base deficit (BD) and lactate, and to determine the odds of operative intervention in penetrating trauma patients. Methods: A prospective observational cohort study was undertaken. Baseline vital signs, BD and lactate were recorded in all patients for whom the trauma team was activated. Pearson correlation and coefficient (ρ) were calculated. ORs were calculated. Results: 75 patients were enrolled. Pearson correlations and coefficients calculated for lactate to systolic blood pressure were: −0.052 (ρ=0.0011, 95% CI −0.225 to 0.228); lactate and HR: 0.23 (ρ=0.0166, 95% CI −0.211 to 0.242); lactate and RR: 0.23 (ρ=0.054, 95% CI −0.174 to 0.277). BD to systolic blood pressure were: 0.003 (ρ=0.00001, 95% CI −0.229 to 0.224); BD and HR: −0.19 (ρ=0.038, 95% CI −0.399 to 0.038); BD and RR: −0.019 (ρ=0.0004, 95% CI −0.244 to 0.208). Odds of operative intervention were greater in patients with abnormally high lactate, OR 4.17 (95% CI 1.57 to 11), but not for BD, OR 2.53 (95% CI 0.99 to 6.45), or any of the vital signs. Conclusions: Triage vital signs have no correlation to lactate or BD levels in penetrating trauma patients. Odds of operative intervention are greater in patients with abnormally high serum lactate levels, but not in those with abnormal triage vital signs or BD.